Pelatihan Penggunaan Aplikasi SPSS untuk Statistik Dasar Penelitian bagi Mahasiswa Se-kota Pontianak - Suprihartini, Lia; Rinaldi, Hasymi; Saputra, Haris Mirza; Sulaiman, Sulaiman; Tandra, Rudy; Krisandi, Samuel Dendy (Politeknik Negeri Pontianak, 2023)
In general, research methodology is divided into quantitative and qualitative methods where quantitative is usually used in exact science studies such as engineering and business, while qualitative is for social humanities studies such as social politics. So that not all higher education students master these two methodologies. This training is specifically designed to provide an understanding of one of the popular research methods, namely the quantitative method related to the use of the SPSS application, especially for students in Pontianak City. Community Service (PPM) is carried out with the aim of being part of increasing the capacity of students in the city of Pontianak regarding understanding the application of SPSS statistics so that it can be better and beneficial for the smooth running of their studies. This activity was held in collaboration with Statistics Indonesia West Kalimantan on July 23 2022 which was attended by approximately 30 participants. Based on the results of the implementation of the PPM activities, it was concluded that with the training activities on the use of this Statistical Application, from the results of observations and observations, students began to open their minds to later try to use Quantitative data processing methods with this SPSS Statistical application. This picture can be seen from the enthusiasm of the participants in carrying out the activity.